Measurement of the shape of the Λ0b→Λ+cμ−νμ¯ differential decay rate - Aaij, R; Adeva, B; Adinolfi, M; Bjørn, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Hancock, T; Harnew, N; Hill, D; Jalocha, P; et al. (American Physical Society, 2017)
A measurement of the shape of the differential decay rate and the associated Isgur-Wise function for the decay Λ0b→Λ+cμ−¯νμ is reported, using data corresponding to 3  fb^−1 collected with the LHCb detector in proton-proton collisions. The Λ+cμ−¯νμ(+anything) final states are reconstructed through the detection of a muon and a Λ+c baryon decaying into pK−π+, and the decays Λ0b→Λ+cπ+π−μ−νμ¯ are used to determine contributions from Λ0b→Λ*+cμ−ν¯ μ decays. The measured dependence of the differential decay rate upon the squared four-momentum transfer between the heavy baryons, q2, is compared with expectations from heavy-quark effective theory and from unquenched lattice QCD predictions.